The Development of Personal Brand in Promoting Business Resiliency in a Selected Sporting Goods Retail Company in Yunnan Province, China - Xu, Bo (Pacific International Journal, 2025)
This study examines the relationship between personal brand development and business resiliency in a sporting goods retail company in Yunnan Province, China. Using a descriptive-correlational design, we analyzed five dimensions of personal branding (social media engagement, content creation, professional expertise, emotional components, and trust) and six aspects of business resiliency (risk management, supply chain resilience, technological integration, soft controls, social capital, and entrepreneurial characteristics). Results showed moderate integration of personal branding among employees, with social media engagement (WM=3.03) and emotional components scoring highest, while trust (WM=2.87) and professional expertise showed room for improvement. Business resiliency was similarly moderate (Overall WM=2.89), with entrepreneurial characteristics (WM=3.18) and social capital (WM=3.01) as strengths, while risk management (WM=2.63) needed attention. A significant positive correlation (r=0.318, p<0.001) was found between personal branding and business resiliency, highlighting their interdependence. Gender and position influenced perceptions, with females rating technological integration higher and senior employees showing stronger entrepreneurial alignment. The findings suggest that targeted personal branding training, enhanced risk management strategies, and fostering an entrepreneurial culture could strengthen organizational resilience. These insights provide practical guidance for retail companies seeking to leverage employee branding for competitive advantage.